Abdominal pregnancy with a live newborn in a low-resource setting: A case report - Olivier Mulisya; Guelord Barasima; Henry Mark Lugobe; Philémon Matumo; Bienfait Mumbere Vahwere; Hilaire Mutuka; Zawadi Léocadie; Wesley Lumika (Elsevier, 2023)
Abdominal pregnancy is defined as pregnancy anywhere within the peritoneal cavity, exclusive of tubal, ovarian, or broad ligament locations. It is a rare form of ectopic pregnancy with high morbidity and mortality for both the mother and the fetus.Diagnosis can be frequently missed in low-resource settings because of poor antenatal healthcare provision, low socioeconomic patient status as well as lack of adequate medical resources. Clinical diagnosis can be difficult and ultrasound scan is helpful during the early stages of gestation but can be disappointing thereafter.A case of abdominal pregnancy in a 25-year-old woman, who presented at 26 weeks of gestation with severe abdominal pain not relieved by any medication, is reported. An emergency laparotomy was undertaken as her vital signs deteriorated. An abdominal pregnancy was found and a live neonate delivered.Ministries of health in developing countries should ensure routine access to ultrasound in early pregnancy. Obstetricians should bear in mind that abdominal pregnancy can present late in gestation.